Barbie is not Born, but Rather Becomes, Barbie - Sue Spaid (Aesthetic Investigations)
I begin this paper by identifying several criticisms of the film Barbie (2023), several of which have been proposed as reasons to deny its feminist content. I then circle back to what I consider the film's most coherent theme, which exemplifies Simone de Beauvoir's best-known quote, `One is not born, but rather becomes, woman.' This claim emphasises that what it is to be a woman is not biological, but social. That is, who we become is influenced by external factors such as family upbringing, available role models, class expectations, and our freedom to navigate our choices. A post-script relates the theme of this film to the current political situation in the U.S., after the re-election of Donald Trump.